Refractive outcome following diode laser versus cryotherapy for eyes with retinopathy of prematurity. - Algawi, K (1994)
The refractive error in 15 eyes with threshold retinopathy of prematurity treated with diode laser photocoagulation was compared with 25 eyes with the same disease severity treated by cryotherapy. Myopia was present in 40% (six eyes) of the first group ranging from -1.50 to -3.50 dioptres; while 92% (23 eyes) showed myopia which ranged from -0.50 to -8.00 dioptres in the cryotherapy group. Sixty per cent (nine eyes) were hypermetropic at less than +3.0 dioptres in the laser group, while only 8% (two eyes) of the cryotherapy group showed hypermetropia. There was no significant difference in astigmatism between the two groups. Eyes with threshold disease treated with diode laser photocoagulation developed significantly less myopia than those treated with cryotherapy (p = 0.0006, two tailed value).